Design and Characterization of Ultrafine-Grained Ferritic and Nanostructured Bainitic Steels Processed by Electropulsing Technique - Bhuyan, Debabrata (IIT(BHU) Varanasi, 2023)
Abstract is available in the attachment.
Keywords: Metallurgical Engineering